2022
DOI: 10.1021/acs.jpcc.2c06672
|View full text |Cite
|
Sign up to set email alerts
|

Discerning the Ultrafast Charge Dynamics in Photostable Perovskite-Carbon Dot Composite Systems: Role of Doped Carbon Dots

Abstract: Photostable perovskite quantum dot (PQD)-based composite systems have huge potential for optoelectronic and photocatalysis applications. Herein, we have synthesized hydrophobic carbon dots (NC-Dots) and made a composite system with PQD to improve the stability of the material and establish a new generation of advanced materials for future applications. However, there is a lack of fundamental understanding of the dynamics and charge separation mechanism in PQD and NC-Dot-based composite systems, which is essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…As per the literature, growth components of GSB signify the possibility of carrier cooling through two different ways and two major ultrafast decay components (τ 1d = 5 ps and τ 2d = 200 ps), and a slow component (τ 3d > 1 ns) appears from the carrier-trapping and recombination process. 27 We observed that the lifetime of the growth component (τ 2g = 0.7 ps) in the PQD−hemin composite becomes slower than that of the PQDs (τ 2g = 0.3 ps), which signifies that the excited state is more populated in the composite system as a result of the resonance of the vibration levels between PQDs and hemin in the excited state. Hot carrier transfer and delocalization of the carriers from hemin toward PQD states can be held liable for such delayed dynamics when the pump energy is high.…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…As per the literature, growth components of GSB signify the possibility of carrier cooling through two different ways and two major ultrafast decay components (τ 1d = 5 ps and τ 2d = 200 ps), and a slow component (τ 3d > 1 ns) appears from the carrier-trapping and recombination process. 27 We observed that the lifetime of the growth component (τ 2g = 0.7 ps) in the PQD−hemin composite becomes slower than that of the PQDs (τ 2g = 0.3 ps), which signifies that the excited state is more populated in the composite system as a result of the resonance of the vibration levels between PQDs and hemin in the excited state. Hot carrier transfer and delocalization of the carriers from hemin toward PQD states can be held liable for such delayed dynamics when the pump energy is high.…”
mentioning
confidence: 76%
“…25,26 In our previous work, we observed that electron transfer was more facile in the PQD−NC dot composite systems, but the process became slower upon the co-doping of P and B in the NC dots as a result of the formation of new PN and BN hybrid states, respectively. 27 Lian's group reported carrier dynamics, such as the carrier-trapping and recombination process and interfacial charge-transfer process within zerodimensional (0D) and two-dimensional (2D) PQDs and molecular electron and hole acceptors. 28,29 Mn-doped perovskites were the most widely reported PQD-based doped materials as a result of their interesting optical, electronic, and magnetic properties.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…8−12 However, similar studies with polyhedral PNCs are largely missing in the literature because of their recent entry. 13,14 Here, we performed a solution phase bimolecular photoinduced charge transfer study in a hybrid of 12…”
Section: ■ Introductionmentioning
confidence: 99%